2016
DOI: 10.1016/j.bbcan.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of orphan nuclear receptors in prostate cancer

Abstract: Orphan nuclear receptors are members of the nuclear receptor (NR) superfamily and are so named because their endogenous physiological ligands are either unknown or may not exist. Because of their important regulatory roles in many key physiological processes, dysregulation of signalings controlled by these receptors is associated with many diseases including cancer. Over years, studies of orphan NRs have become an area of great interest because their specific physiological and pathological roles have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 155 publications
(198 reference statements)
1
25
0
Order By: Relevance
“…These receptors can either bind directly to their specific REs as monomers, which bind to a single half site, or in conjunction with RXR as a heterodimer . The orphan receptor family includes chicken ovalbumin upstream promoter transcription factor 2 (COUP‐TFII), estrogen‐related receptor alpha (ERRα), dosage‐sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1 (DAX1), and Retinoic Acid Receptor (RAR)‐related orphan receptor gamma (RORγ) . Because of their critical regulatory roles in many key physiological processes, dysregulation of important signaling pathways controlled by these receptors is associated with many diseases, including cancer .…”
Section: Nuclear Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors can either bind directly to their specific REs as monomers, which bind to a single half site, or in conjunction with RXR as a heterodimer . The orphan receptor family includes chicken ovalbumin upstream promoter transcription factor 2 (COUP‐TFII), estrogen‐related receptor alpha (ERRα), dosage‐sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1 (DAX1), and Retinoic Acid Receptor (RAR)‐related orphan receptor gamma (RORγ) . Because of their critical regulatory roles in many key physiological processes, dysregulation of important signaling pathways controlled by these receptors is associated with many diseases, including cancer .…”
Section: Nuclear Receptorsmentioning
confidence: 99%
“…17 Because of their critical regulatory roles in many key physiological processes, dysregulation of important signaling pathways controlled by these receptors is associated with many diseases, including cancer. 17 In addition, evidence suggests that orphan NRs play essential roles in the innate immune response and help to prevent pathogenic inflammatory responses and enhance antimicrobial host defense. 18 It has been suggested that identification of new functions for the orphan NRs could facilitate development of novel preventive and therapeutic strategies against human inflammatory diseases (reviewed in the work of Jin et al 18 ).…”
Section: Orphan Receptorsmentioning
confidence: 99%
“…Similarly, increasing the expression of peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PPARGC1A), the protein ligand of ESRRA, increases energy expenditure and reduces obesity [23]. So far, most previous studies of ESRR actions have focused on its role in cancer progression and this topic has been reviewed elsewhere [24][25][26][27][28][29][30][31][32][33][34][35]. There have also been a few studies on its roles in bone and muscle differentiation [36][37][38], trauma/shock [39], and infection [40].…”
Section: Introductionmentioning
confidence: 99%
“…TLX has been reported to have a role in overcoming senescence (oncogene induced and PTEN-loss induced) in multiple tumour types including prostate, as it can repress p21 and activate SIRT1, both of which are prominent senescence-related genes (Wu et al 2015). This role in senescence may make TLX an important factor in cancer progression and CRPC, where senescence is thought to be a vital part of tumour resistance to treatment and recurrence, and Wu and coworkers suggest that TLX may promote the self-renewal and maintenance of cancer stem cells (Wu et al 2016a). Further research into the role of TLX in prostate cancer progression is clearly needed, especially as in our analysis of TCGA data (Fig.…”
Section: :11 Tlx (Aka Tll or Nr2e1)mentioning
confidence: 99%
“…This, however, does not preclude the possibility of modifying their activity using synthetic compounds and small molecules, and so they are potential drug targets in cancer and other diseases. A recent review has covered orphan receptors in prostate cancer in detail (Wu et al 2016a), so here we will focus on a small number of prominent receptors, which were identified as highly altered in our TCGA analysis.…”
Section: Orphan Receptorsmentioning
confidence: 99%